Pengaruh Digital Financial Literacy, Financial Self-Efficacy terhadap Keputusan Investasi Saham di Kota Bekasi - Sopian, Sopian; Abdilah, Abdilah (Journal of Management and Creative Business, 2026)
This study aims to examine the effect of Digital Financial Literacy and Financial Self-Efficacy on Investment Decisions among stock investors in Bekasi City. The rapid development of digital financial services has increased public access to investment products and financial information. However, the quality of investment decisions is not only determined by access to technology but also by an individual’s ability to understand digital financial information and confidence in managing personal finances. This research employed a quantitative approach using a survey method. Data were collected through questionnaires distributed to 100 respondents who had experience investing in the stock market. The sampling technique used was purposive sampling, while data analysis was conducted using multiple linear regression. The findings indicate that Digital Financial Literacy has a positive and significant effect on Investment Decisions. Investors with higher levels of digital financial literacy tend to have better abilities to evaluate financial information, assess risks, and select appropriate investment instruments. Furthermore, Financial Self-Efficacy also has a positive and significant effect on Investment Decisions. Individuals who possess stronger confidence in their financial management capabilities are more likely to make rational and well-considered investment choices. Simultaneously, Digital Financial Literacy and Financial Self-Efficacy significantly influence Investment Decisions. These findings imply that improving digital financial knowledge and strengthening financial self-confidence are essential for enhancing the quality of investment decision-making. The results of this study provide valuable insights for policymakers, financial institutions, educators, and investors in promoting sustainable investment behavior in the digital era.